2011
DOI: 10.1063/1.3604395
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic manipulation of ribosomal RNA

Abstract: The manipulation of ribosomal RNA ͑rRNA͒ extracted from E. coli cells by dielectrophoresis ͑DEP͒ has been demonstrated over the range of 3 kHz-50 MHz using interdigitated microelectrodes. Quantitative measurement using total internal reflection fluorescence microscopy of the time dependent collection indicated a positive DEP response characterized by a plateau between 3 kHz and 1 MHz followed by a decrease in response at higher frequencies. Negative DEP was observed above 9 MHz. The positive DEP response below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
(34 reference statements)
1
46
0
Order By: Relevance
“…Such an effect has also been reported for viruses , metallic nanoparticles , and protein molecules . In a study on the dielectrophoretic collection of RNA, Giraud et al found the expected square dependence on voltage starting at a threshold voltage. A detailed theory on the interplay between DEP and Brownian motion has been developed by Ramos et al .…”
Section: Resultsmentioning
confidence: 65%
“…Such an effect has also been reported for viruses , metallic nanoparticles , and protein molecules . In a study on the dielectrophoretic collection of RNA, Giraud et al found the expected square dependence on voltage starting at a threshold voltage. A detailed theory on the interplay between DEP and Brownian motion has been developed by Ramos et al .…”
Section: Resultsmentioning
confidence: 65%
“…20 However, DEP trapping within media of high conductivity for enhancement of DNA hybridization kinetics poses distinct challenges. The enhanced current flow under applied fields within media of high conductivity (1 S/m) causes Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…0 f MHz and the probe frequencies spanning the range, 4 1 f MHz. Time dependent collection profiles for each of the control and probe cycles were quantified by linear fitting (fourteen data points) that approximates an exponential series for sufficiently short time intervals [4,[8][9][10][11][12][13][14][15][16]. The initial collection rate ratio of …”
Section: Resultsmentioning
confidence: 99%
“…The initial collection rate is approximately proportional to the small-time averaged DEP force [4,[8][9][10][11][12][13][14][15][16] [5,7] and all other symbols have their usual meanings. Usually the DEP force is switched on for a limited time (up to a minute) then switched off.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation